An adapted serial reaction time task for procedural learning measurements - Sengottuvel, K (Springer India, 2013)
Serial Reaction Time (SRT) task is a visuomotor task to measure sequence learning. Several modifications of SRT task were used in the past. Traditional SRT tasks provided sequence learning measure at one instance only. Moreover, traditional SRT tasks did not use consistent measures to rule out attention factors contributing to SRT scores. The present study aims to design an Adapted SRT (AD-SRT) task with provisions to measure progress in sequence learning over trials. It is hypothesized that measures of sequence learning over several trials and intervals of SRT task could reflect on sequence learning ability in children with language impaired. The study design includes two choice reaction time task (TCRT) as a measure of baseline performance of attention. The AD-SRT task design, its ability to measure progress in sequence learning and its relation to attention measures are discussed in detail.